Assessment of competitiveness of the airport "Boryspil" through SPACE-analysis - Rohanova, Hanna; Panchoshna, Tatiana (My University, 2020)
To determine an effective strategy for the development of SE "International airport "Boryspil" we realized SPACE-analysis of company. In the classic SPACE-analysis system consists of four groups of criteria for evaluating enterprise; the indicators were applied weights
Keywords: конкурентоспроможность; аеропорт; SPACE analysis; airport; авіаперевезення; кафедра фінансів